PHYSICAL COMPUTATION: From the Turing machine to the Universe: Da Máquina de Turing ao Universo - Michelin, José Vitor (Revista Interface Tecnológica, 2025)
This paper discusses the relationship between computation, physics, and information, analyzing how the notion of the Turing machine, computability theory, and computational complexity are connected with physical limits and quantum possibilities. It is based on the principle that information has a physical dimension, and that computational operations are intrinsically linked to thermodynamic processes. The hypothesis is discussed that the universe can be seen as a quantum computational system, in which physical phenomena emerge from the processing of information. It is concluded that computation, far from being merely a formal or technological construct, constitutes a fundamental physical process capable of offering new perspectives for understanding reality.